If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -2x = 2x + -5x Combine like terms: 2x + -5x = -3x 8 + -2x = -3x Solving 8 + -2x = -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 8 + -2x + 3x = -3x + 3x Combine like terms: -2x + 3x = 1x 8 + 1x = -3x + 3x Combine like terms: -3x + 3x = 0 8 + 1x = 0 Add '-8' to each side of the equation. 8 + -8 + 1x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 1x = 0 + -8 1x = 0 + -8 Combine like terms: 0 + -8 = -8 1x = -8 Divide each side by '1'. x = -8 Simplifying x = -8
| 1x+3(4)=48 | | 9(-10)+160= | | -6h+2=-46 | | x+7=-3+3x | | .60x+.30(90)=.50(x+90) | | 6=18b | | 3x+15=12b-3b | | x*-5=10 | | 16t^2-128+400=0 | | 2a+24-3a=5a | | 8p-4=7p-2 | | n^2-34n-251=0 | | t^2-8+25=0 | | 1-m=1-m | | 16.28+8=100 | | -4n+2=-13-7n | | x^7-5x+6=0 | | 13x+23y=-5 | | -6+4p=5p-4 | | -3+2x-9=9 | | -10(3+2)-7= | | 569.7844=3135.6289h | | v+4=3v-6 | | 2=-2x+25 | | -7x=-16 | | 12+x-2x=-4+x | | 5s-11=13+s | | f(x+7)=x^2+8x+5 | | -7-7x=-16 | | 12x+6=x | | 5v-2=2+2v-2+1 | | -18=-2+2w |